Research on Teaching Method of Computer Application Course Based on Evidence-based Teaching Method. Issue 3 (October 2020) - He, Yong; Li, Yizhi
Abstract: The basis of computer application is not only useful for office automation, but also useful for the study of cognitive disciplines. For example, if you learn how to surf the Internet, you will use network resources to collect Chinese extracurricular books and find relevant literature. The experimental research includes the design of questionnaire survey, the development of teaching practice, the collection and collation and analysis of experimental data. This paper demonstrates the effectiveness of evidence-based teaching in computer application experiment teaching through sufficient data.